AFFIRMATION OF RADICAL RELIGIOUS ATTITUDES BY MEANS OF SOCIAL NETWORKS (International Journal of Contemporary Security Studies, 2022)
From the earliest forms of life until today, man is in constant need of means that would enable simpler and faster communication. The evolution of the brain and natural intelligence, as well as the technological revolution and the development of artificial intelligence, originally for military purposes, created such conditions that allowed oral communication, which involved physical presence, to be replaced by virtual, which is completely unconditional in this respect, and requires only minimum resources to be practiced. In such an atmosphere, especially in the beginning of the 21st century, there has been an expansive growth of offers of new forms of communication, where, judging by the number of users and importance for a modern, practical life, social networks have managed best. The viral use of these platforms for social interaction and their unstoppable progress have gone a few steps ahead of the possibilities of mankind, bearing the consequence that these users often find themselves in the role of victims of unfinished or superficially implemented process of shaping social networks into a comprehensive normative district. Empirical research conducted using a survey questionnaire showed that users of social networks are constantly exposed to some form of intolerant or violent behavior, and that part of such behavior is based on extremely radical religious attitudes. However, verbal violence accompanied by religious motives, when it comes to social networks, is not a systemic and organized activity, although it shows the potential to become so at some point, but is part of an extremist opus that includes discrimination based on other criteria of diversity.
Keywords: social networks, radicalism, extremism, attitudes, religion, technology, communication.